Violencia familiar y conducta antisocial en adolescentes de secundaria de la Institución Educativa Claverito Iquitos 2024 - Jaramillo Molano, Jennyfer Rosa (2024)
The objective was to determine the relationship that exists between family violence and antisocial behavior in adolescents in the 5° grade of secondary school at the Claverito educational institution, Iquitos 2024. The type of research was quantitative, descriptive, correlational; and non-experimental, transversal design, with a population of 102 students. The technique used was the survey. The instruments used were: Family Violence Questionnaire (CVIFA) and Self-Reported Antisocial Behavior Questionnaire (SRA). The Excel program was used for the database and the Jamovi statistical program for processing 2.3.28 Spanish version was used to perform descriptive and inferential statistics. The data are presented in tables and graphs of means, frequencies and percentages. For the hypothesis test, ANOVA was applied as a result of X2 Friedman df 1 p< 0.05. The main results indicate: 89 (87.3%) adolescents presented a medium level of family violence, 8 (7.8%) a low level of family violence and 5 (4.9%) a high level of family violence. Likewise, 98 (96.1%) presented antisocial behavior and in 4 (3.9%) antisocial behavior was absent. What can be deduced is that the majority of adolescents presented antisocial behavior and a medium level of family violence. Therefore, it is concluded that there is a significant relationship between family violence and antisocial behavior in adolescents from the Claverito Educational Institution, Iquitos, year 2024.